The Kuparuk Pingo Site: a Northern Archaic Hunting Camp of the Arctic Coastal Plain, North Alaska - Lobdell, John E. (ARCTIC, 1986)
A single-component caribou hunting camp, located on a subsiding pingo near the mid-Beaufort Sea coast of North Alaska, yielded a radiocarbon date of almost 6000 years. The Kuparuk Pingo site revealed evidence for use of the Arctic Coastal Plain by peoples of the Northern Archaic tradition and provides a cultural chronological marker for indicating the potential longevity of pingos. Trade lithic materials from interior Alaska and the presence of bone refuse and bone tools due to the excellent preservation conditions of a pingo environment expanded the knowledge of these intermediate age cultural times in the North.Key words: Northern Archaic tradition, Arctic Coastal Plain, pingo, caribou, North Alaska Mots clés: tradition archaïque du Nord, plaine de la côte arctique, pingo, caribou, Nord de l'Alaska